BIBLIOTECA PUBLICĂ 2015: POLITICI, ORIENTĂRI STRATEGICE, TENDINȚE - OSOIANU, director adjunct, Biblioteca Națională a RM, Vera (BIBLIOPOLIS, 2020)
At present, the European model of libraries development is attractive because it is based on the fundamental values of the European Union, set out in the Treaty of Lisbon: human dignity, freedom, democracy, equality, legal status etc. These values are common to all states, and any European country wishing to join the Union must comply them. At various stages, libraries have been involved in projects such as PULMAN, LibEcon, CALIMERA etc. All national regulation documents developed following the library reform were based on documents and standards promoted international and European level. So, studies, articles published in the country were based on documents approved internationally, such as UNESCO School libraries Manifesto (2005); Berlin Declaration on Open Access to Knowledge in the Sciences and Humanities (2003); IFLA Glasgow Declaration on Libraries, Information Services and Intellectual Freedom (2002); IFLA Internet Manifesto (2014) etc. The development projects initiated by community, are most effective when they are based on existing resources and local institutions that people know and trust, such as public libraries. Libraries are strong because they have public support and a minimal funding. Therefore, the different authorities and development agencies should better support services provided by libraries, than invest in new infrastructure. In the situation of the rapid technology development and modernization all library development strategies must start from the idea that the library is no longer the unique promoter of information and electronic connectivity to community members.